(untitled) (Religious dialogue and cooperation, 2021)
Intervention in helping professions involves a lot more than knowledge-based methods and skills adopted by professionals, often it involves exchange of ideas, feelings, beliefs, and values that may or may not be directly addressed or acknowledged, but have profound influence in the process of recovery or reestablishment of the wellbeing of clients. We will try to prove the link between Christianity and contemporary society values such as individual freedom, right to service (human right), social justice, human dignity, professional integrity, and subsidiarity. Christian spiritual perspective accepts the belief that God exists and that He created the entire universe, including the material and spiritual realms. These spheres are in mutual coexistence, reflecting intelligent creation, and exist in reality independent of humanity. In the created order, humans are ontologically unique, created in the image of God. Common to all people is their dignity, value, personality, creativity, strengths, and rationality. The value of human differences and autonomy is an important ideal that is emphasized in Christian spiritual perspective in understanding human uniqueness and individuality. Christian spiritual perspective will be therefore seen as a resource that promotes client efforts to solve or deal with problems. The Christian spiritual perspective can be used as part of therapeutic approaches in counseling models based on empowering strengths and recognizing the role of life events in the therapy, an interactive process in which individuals construct their meaning on the basis of life experiences.